EVALUASI RESERVOIR BATURAJA PADA LAPANGAN FALCON DENGAN MENGGUNAKAN SIMULASI RESERVOIR UNTUK MEMAKSIMALKAN PRODUKSI - Gerdha Agreska Lubis Agreska Lubis; Maman Djumantara (Jurusan Teknik Perminyakan Fakultas Teknologi Kebumian dan Energi Universitas Trisakti, 2016)
Falcon Field begins with the discovery of the GG-1 wells are explored in August 1974. The program DST performed on one zone at Falcon Field in the Baturaja Formation producing 429 BOPD and 0.14 MMCFD. Then in 1978, Falcon Field was developed by constructing three wells on the platform GGA and in 1988 made eight more wells on the platform GGB. Falcon Field is the peak production in 1978 amounted to 5670 BOPD. Currently Falcon Field still in production of 1000 BOPD and 451 MCFPD of four wells. Cumulative production in January 2014 at 10.57 and 9.08 MMCF MMBO, and Recovery Factor is currently at 19.2%. Based on the structure map and well log correlation, Baturaja in Falcon Fields has anticline structure with orientation North-South fault. The thickness of zone has 1000 ft ( 300 m) with oil column around 100 ft. To conduct field production performance predictions in the future, needs to be done the reservoir simulation modeling where the results are expected to represent the true reservoir model. Grid made in this model has a cell size of 50 mx 50 m with a thickness of 3 ft, 53 layers, and a total of about 650000 cell active cell. In the early, the validation of model is carried out for the initialization by using the Black Oil Simulator model. Initialization is intended to build initial equilibrium of the total hydrocarbon reservoir with the volume control of hydrocarbon static model calculations. The alignment stages of model or History Matching is done to see if the reservoir model that has been created to represent the actual condition of the reservoir. From the simulation reservoir the number of OOIP is 55.07 MMSTB, while OOIP with the static model is 55.2 MMSTB with a difference of 0.2 %. For the development of the Falcon Fields in the Reservoir Baturaja, the study wasperformed under planned five scenarios, namely the first scenario (base case), the second scenario (base case with the addition of rework moving field), the third scenario (Base case with wellwork and infill), the fourth scenario (Modeling Drawdown), and the fifth scenario (Modeling Downhole Water Sink). Scenario production started in January 2014 until January 2037 for 23 years with the aim to provide maximum drainage. Falcon Field production forecasting results for the first scenario, the second scenario, the third scenario, the fourth scenario, and scenarios fifth consecutive MMSTB of 12.87, 14.66 MMSTB, 15.3 MMSTB, MMSTB 14.01, 14.17 MMSTB with consecutive RF 23:37%, 26.62% , 27.78%, 25.44%, and 25.73%.